Carbon-coated hard carbon / chiral silica composite material and preparation method and application thereof, sodium ion battery

By using carbon-coated hard carbon/chiral silica composite in sodium ion batteries, the problems of low capacity and poor circulation performance of amorphous hard carbon materials are solved, and higher battery capacity and stability are achieved, improving Overall performance of sodium ion batteries.

CN118867213BActive Publication Date: 2024-12-31ANHUI ESTONE MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411367711.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-31
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Amorphous hard carbon materials have problems such as low capacity, poor circulation performance and unstable structural problems in the negative electrode materials of sodium ion batteries, resulting in reduced battery capacity and insufficient cycle stability.

Method used

Using carbon-coated hard carbon/chiral silica composite, chiral silica is formed by in situ in the holes of hard carbon material and polymer coated on its surface to form a dense carbon layer to reduce the specific surface area. and inhibit the volume expansion of silica.

Benefits of technology

It improves the circulation efficiency and service life of sodium ion batteries, enhances the first-circle Coulomb efficiency of the battery, and effectively suppresses the volume expansion of silica, improving the electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118867213B_ABST
    Figure CN118867213B_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-coated hard carbon / chiral silica composite material, a preparation method and application thereof, and a sodium ion battery, and relates to the technical field of sodium ion batteries. The invention adopts a sol-gel method to in-situ generate chiral silica in the pores of a hard carbon material, effectively suppressing the volume expansion of silica during an electrochemical reaction, and improving the cycle efficiency and service life of the battery; and uses a polymer to coat the outer layer of the hard carbon / chiral silica composite material to form a dense carbon layer, thereby reducing the specific surface area of ​​the material, improving the first-cycle coulomb efficiency of the battery, and suppressing the volume expansion of silica.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a carbon-coated hard carbon / chiral silicon dioxide composite material, a preparation method and application thereof, and a sodium ion battery. Background Art

[0002] As the greenhouse effect and environmental pollution caused by the continuous consumption of traditional fossil energy become increasingly serious, renewable clean energy (such as solar energy and wind energy) faces new opportunities and challenges. However, renewable energy has intermittent and regional defects and requires the assistance of large-scale energy storage systems, which puts higher requirements on sustainable and low-cost energy storage technologies. Due to the abundant reserves of sodium resources, sodium-ion batteries have attracted more and more attention in recent years and are considered to be a beneficial supplement to lithium-ion batteries in the field of large-scale energy storage. Therefore, the development of anode materials with excellent performance, low cost and easy availability is of great significance to the industrialization of sodium-ion batteries.

[0003] Sodium-ion batteries mainly include positive electrodes, negative electrodes, electrolytes, and separators. Among them, the negative electrode material is the key to determining battery performance. The development of negative electrode materials for sodium-ion batteries has gone through a relatively long process, and the research objects can be divided into two categories: carbon-based and non-carbon materials. Carbon-based materials mainly refer to amorphous hard carbon materials, and non-carbon materials mainly refer to titanium-based materials and alloy materials. In lithium-ion batteries, graphite is a commonly used negative electrode material, but because the sodium storage capacity of graphite is too low, it cannot be used as a negative electrode material for sodium-ion batteries; on the contrary, amorphous hard carbon has a low sodium storage potential, moderate sodium storage capacity, and a small volume deformation after sodium insertion, and good cycle performance. It has the best comprehensive performance among many candidates. From the perspective of raw materials, amorphous hard carbon precursors are widely available and easy to prepare. Therefore, amorphous hard carbon is most likely to be the first to achieve industrialization in the field of negative electrode materials for sodium-ion batteries, but there are still the following problems in the application of amorphous hard carbon negative electrode materials:

[0004] (1) Amorphous hard carbon materials have a large specific surface area. During the first electrochemical process, a large amount of sodium will be consumed, a large number of irreversible reactions will occur, and the SEI film will be generated, which will reduce the battery capacity.

[0005] (2) The capacity provided by amorphous hard carbon material negative electrode is relatively low, which hinders its further application.

[0006] (3) The structure of amorphous hard carbon materials is unstable. After electrochemical cycling, the structure may collapse, the cycle stability will be destroyed, and the capacity will also be reduced. Summary of the invention

[0007] In order to solve the problems of low capacity, poor cycle performance and poor cycle stability of hard carbon negative electrode materials of sodium ion batteries, the present invention provides a carbon-coated hard carbon / chiral silica composite material and a preparation method thereof.

[0008] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0009] One of the objects of the present invention is to provide a carbon-coated hard carbon / chiral silica composite material, comprising a core and a shell, wherein the core is a hard carbon / chiral silica composite material, the shell is carbon, and the hard carbon / chiral silica composite material is a porous hard carbon material with embedded chiral silica.

[0010] The second object of the present invention is to provide a method for preparing a carbon-coated hard carbon / chiral silica composite material, comprising the following steps:

[0011] (1) In a solution containing a chiral inducing agent, chiral silica is in situ generated in the pores of a hard carbon material by a sol-gel method to obtain a hard carbon / chiral silica composite material;

[0012] (2) Coating a polymer on the surface of the hard carbon / chiral silica composite material and carbonizing it at high temperature to obtain a carbon-coated hard carbon / chiral silica composite material.

[0013] The third object of the present invention is to provide a method for preparing a hard carbon material, comprising the following steps:

[0014] (1) subjecting a carbon source, a modifier and a pore-forming agent to a hydrothermal reaction to obtain a precursor;

[0015] (2) After the precursor and the activator are evenly mixed, they are calcined at high temperature under the protection of an inert gas to obtain a hard carbon material.

[0016] A fourth object of the present invention is to provide an application of the carbon-coated hard carbon / chiral silica composite material in a sodium ion battery.

[0017] The fifth object of the present invention is to provide a sodium ion battery, comprising a positive electrode, a negative electrode and a separator, wherein the negative electrode comprises a negative electrode active material, and the negative electrode active material comprises the carbon-coated hard carbon / chiral silica composite material.

[0018] The beneficial effects of the present invention are:

[0019] 1. The present invention adds a chiral inducing agent during the synthesis of silicon dioxide to generate chiral silicon dioxide. The chiral silicon dioxide enhances the conductivity of silicon dioxide and also inhibits the volume expansion of silicon dioxide, thereby improving the cycle efficiency and service life of the battery.

[0020] 2. The present invention adopts an in-situ decomposition and synthesis method to make the silica gel and the hard carbon material react, allowing the silica gel to form in the cross-linked interpenetrating network pores, which can effectively inhibit the volume expansion of silica during the electrochemical reaction. At the same time, the synthesized silica has a small particle size. Embedding silica into the prepared hard carbon skeleton can alleviate its volume expansion effect.

[0021] 3. The present invention also utilizes a polymer to coat the outer layer of the hard carbon / chiral silica composite material. After carbonization, the polymer forms a dense carbon layer on the surface of the hard carbon / chiral silica composite material, thereby reducing the specific surface area of ​​the material, improving the first-cycle coulomb efficiency of the battery, and also inhibiting the volume expansion of silica. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the XRD pattern of the hard carbon material prepared in Example 1;

[0023] Figure 2 This is a BET diagram of the hard carbon material prepared in Example 1;

[0024] Figure 3 This is a BET diagram of the carbon-coated hard carbon / chiral silica composite material prepared in Example 1;

[0025] Figure 4 This is a SEM image of the hard carbon material prepared in Example 1;

[0026] Figure 5 This is a SEM image of the hard carbon material prepared in Example 9;

[0027] Figure 6 This is a SEM image of the hard carbon material prepared in Example 6;

[0028] Figure 7 The SEM images of the hard carbon / chiral silica composite material prepared in Example 1 at different magnifications;

[0029] Figure 8 This is a SEM image of the carbon-coated hard carbon / chiral silica composite material prepared in Example 1;

[0030] Fig. 9 The charge / discharge cycle curves of the sodium ion batteries assembled in Example 1 and Comparative Example 13;

[0031] Fig.10 The charge / discharge cycle curves of the sodium ion batteries assembled from Example 1, Comparative Examples 10 and 14. DETAILED DESCRIPTION

[0032] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.

[0033] The present invention provides a carbon-coated hard carbon / chiral silica composite material, comprising a core and an outer shell, wherein the core is the hard carbon / chiral silica composite material, the outer shell is carbon, and the hard carbon / chiral silica composite material is a porous hard carbon material with embedded chiral silica.

[0034] The present invention provides a method for preparing a carbon-coated hard carbon / chiral silica composite material, comprising the following steps:

[0035] (1) In a solution containing a chiral inducing agent, chiral silica is in situ generated in the pores of a hard carbon material by a sol-gel method to obtain a hard carbon / chiral silica composite material;

[0036] (2) Coating a polymer on the surface of the hard carbon / chiral silica composite material and carbonizing it at high temperature to obtain a carbon-coated hard carbon / chiral silica composite material.

[0037] In the present application, the binder can be adsorbed on the inducer, so that the silicate can be stably adsorbed on the surface of the inducer during the hydrolysis process, thereby forming chiral SiO2. The chiral inducer has a special chiral structure, and the special structure of the chiral inducer will not be destroyed during the reaction process. Through the action of PEI, the SiO2 synthesized by hydrolysis of TEOS is synthesized in situ thereon, so that the SiO2 has a corresponding chiral structure. Further, the solution containing the chiral inducer is an aqueous solution of the binder and the chiral inducer, wherein the mass ratio of the binder to the chiral inducer is 1: (0.1~2), for example, it can be 1: 0.1, 1: 0.2, 1: 0.3, 1: 0.5, 1: 0.8, 1: 1, 1: 1.2, 1: 1.5, 1: 1.8, 1: 2 or any value in the range formed by any two of the above ratios.

[0038] Further, the binder includes but is not limited to at least one of polyethyleneimine (PEI), polyvinyl alcohol (PVA), and polyethylene glycol (PEG). Further, the chiral inducing agent includes but is not limited to at least one of L-tartaric acid, L-alanine, L-valine, L-lysine, and L-glutamic acid.

[0039] Furthermore, the sol-gel method uses silicate as raw material, water as solvent, ethanol as co-solvent, and acid or base as catalyst. Specifically, the reaction temperature of the sol-gel method is 60-80°C, and the reaction time is 2-12 h; the molar ratio of the silicate to ethanol and water is 1: (80-120): (10-50); the acid includes but is not limited to at least one of hydrochloric acid (HCl), nitric acid (HNO3), phosphoric acid (H3PO4), and acetic acid (CH3COOH); the base includes but is not limited to at least one of ammonia water, sodium hydroxide (NaOH), and potassium hydroxide (KOH).

[0040] Furthermore, the content of chiral silica in the hard carbon / chiral silica composite material is 1-40%, for example, it can be 1%, 5%, 10%, 15%, 18%, 20%, 23%, 25%, 30%, 35%, 40% or any value in the range formed by any two of the above ratios, preferably 15-25%, and more preferably 23%.

[0041] Furthermore, the polymer includes but is not limited to at least one of polyacrylonitrile (PAN), polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene glycol, phenolic resin, asphalt and polyamic acid. In the present invention, there is no special restriction on the coating method in step (2), including but not limited to in-situ polymerization coating and emulsion coating. The emulsion coating method is: the hard carbon / chiral silica composite material and the polymer emulsion are mixed evenly and then dried, that is, the polymer can be coated on the surface of the hard carbon / chiral silica composite material.

[0042] Furthermore, the mass ratio of the hard carbon / chiral silica composite material to the polymer is 1:(1~3), for example, it can be 1:1, 1:1.5, 1:2, 1:2.5, 1:3 or any value in the range formed by any two of the above ratios.

[0043] Furthermore, the high temperature carbonization temperature is 800-1200°C, the holding time is 2-5 hours, and the heating rate is 3-7°C / min. The polymer is carbonized under high temperature conditions to form a carbon coating layer on the surface of the hard carbon / chiral silica composite material.

[0044] The present invention provides a method for preparing a hard carbon material, comprising the following steps:

[0045] (1) subjecting a carbon source, a modifier and a pore-forming agent to a hydrothermal reaction to obtain a precursor;

[0046] (2) After the precursor and the activator are evenly mixed, they are calcined at high temperature under the protection of an inert gas to obtain a hard carbon material.

[0047] Furthermore, the carbon source includes but is not limited to at least one of sucrose, glucose, fructose and maltose. Sugars are plant-based carbon sources with the characteristics of wide sources and low prices; and the hard carbon derived from sugars has a stable structure, uniform morphology, high carbon content and strength.

[0048] Furthermore, the modifier includes but is not limited to at least one of sodium polyacrylate (PAANa) and sodium carboxymethyl cellulose (CMC-Na). The carbon source is modified by the modifier to generate a cross-linked interpenetrating network. A large number of pores are distributed in the cross-linked interpenetrating network matrix, which is conducive to the electrolyte entering the active material without being restricted by charge transfer. This structure can promote the penetration of electrolytes and ion diffusion; the pore wall thickness caused by the interpenetrating network becomes smaller, and this short diffusion distance is conducive to Na + Insertion and deintercalation of ions.

[0049] Furthermore, the pore-forming agent includes but is not limited to at least one of ammonium fluoride (NH4F) and ammonium chloride (NH4Cl). During the hydrothermal reaction, the pore-forming agent is decomposed by heat to form ammonia, hydrogen fluoride or hydrogen chloride, forming a rich pore structure in the precursor, enriching the Na + Embedded active site.

[0050] Furthermore, the temperature of the hydrothermal reaction is 150-170° C., and the time is 8-10 h.

[0051] Furthermore, the usage ratio of the carbon source, the modifier and the pore-forming agent is (0.2~1) mol: (0.15~1) g: (0.1~0.5) g.

[0052] Furthermore, the activator includes but is not limited to at least one of KOH, NaOH, potassium carbonate (K2CO3), zinc chloride (ZnCl2), and H3PO4. The activator can enrich and expand the formed through-holes, which is beneficial to the formation of chiral silica in the subsequent holes.

[0053] Furthermore, the mass ratio of the precursor to the activator is 1: (1-3).

[0054] Furthermore, the mixing method is ball milling, the ball-to-material ratio is (5-20): 1, the ball milling time is 6-12 h, and the rotation speed is 200-600 rpm.

[0055] Furthermore, the inert gas is selected from at least one of nitrogen, helium and argon.

[0056] Furthermore, the high temperature calcination temperature is 700-1200°C, the holding time is 1-5 h, and the heating rate is 3-7°C / min.

[0057] The present invention provides application of the carbon-coated hard carbon / chiral silicon dioxide composite material in a sodium ion battery.

[0058] The present invention also provides a sodium ion battery, comprising a positive electrode, a negative electrode and a separator, wherein the negative electrode comprises a negative electrode active material, and the negative electrode active material comprises the carbon-coated hard carbon / chiral silica composite material.

[0059] The present invention has no special limitation on the positive electrode and the separator of the sodium ion battery, which are known to those skilled in the art and will not be described in detail herein.

[0060] In the present invention, the negative electrode includes a negative electrode active material, a conductive agent and a binder. The types of the conductive agent and the binder are known to those skilled in the art.

[0061] The technical solution of the present invention is described in detail below through specific embodiments.

[0062] In the following examples, DMF is N,N-dimethylformamide; TEOS is tetraethyl orthosilicate.

[0063] Example 1

[0064] (1) Preparation of precursor:

[0065] Weigh 13.68 g of sucrose and stir to dissolve it in 100 mL of deionized water (sucrose concentration is 0.4 mol / L), then add 0.4 g of PAANa and 0.3 g of NH4F, mix well and transfer to the reactor, and hydrothermally react at 170°C for 8 h. After the reaction, cool the reactor naturally to room temperature, take out the mixture in the reactor, filter and wash it with deionized water and ethanol until the filtrate is neutral, and dry the residue in a 60°C oven for 12 h to obtain the precursor.

[0066] (2) Preparation of hard carbon materials:

[0067] The precursor and KOH were ground uniformly in a mass ratio of 1:2, and then put into a planetary ball mill for ball milling, with a ball-to-material ratio of 10:1, a ball milling time of 8 h, and a rotation speed of 500 rpm. The mixture obtained by ball milling was placed in a tubular furnace for calcination, kept at 800°C for 2 h, and the heating rate was 5°C / min. After cooling naturally to room temperature, the calcined product was taken out, placed in a 0.5 mol / L HCl solution and stirred for 12 h, filtered, and repeatedly washed with deionized water and ethanol until the filtrate was neutral, and the filter residue was dried in an oven at 80°C to obtain a hard carbon material.

[0068] (3) Preparation of hard carbon / chiral silica composite materials:

[0069] 0.5 g of polyethyleneimine (PEI) was dissolved in 100 mL of water at 60°C by stirring, and then mixed with 100 mL of aqueous solution containing 0.5 g of L-tartaric acid at 100°C for 5 min, cooled naturally to room temperature, and then the pH value was adjusted to 4, sealed, and allowed to stand at 5°C for 12 h. After standing, a lower precipitate and a supernatant were formed. The lower precipitate was centrifuged and washed with water to obtain PEI / L-tartaric acid. 0.3 g of PEI / L-tartaric acid was dissolved in 3 mL of water to obtain a solution containing a chiral inducer.

[0070] Weigh 2 g of the hard carbon material prepared in step (2) and mix it with 1.10 mL of TEOS, add 5 mL of ethanol to dissolve it, and prepare solution A; mix 0.8 mL of deionized water, 36 mL of ethanol and 1 mL of the above solution containing the chiral inducer evenly, and adjust the pH to 9 with ammonia water to prepare solution B; mix solution B with solution A at 75°C, react at a speed of 800 rpm for 12 h, and after the reaction is completed, centrifuge the reaction solution, wash and dry the precipitate to obtain a hard carbon / chiral silica (C / *SiO2) composite material.

[0071] (4) Preparation of carbon-coated hard carbon / chiral silica composites:

[0072] The C / *SiO2 composite material prepared in step (3) and PAN were ground at a mass ratio of 1:2 for 30 min, poured into DMF and stirred to completely dissolve PAN, the resulting mixture was heated, the solution was evaporated by stirring, the remaining solid product was ground into fine powder, and then placed in a tubular furnace for high-temperature calcination under a nitrogen atmosphere, the temperature was raised to 1100°C and kept for 5 h, and the heating rate was 5°C / min. After natural cooling, the calcined product was taken out, ground, and crushed to obtain a carbon-coated hard carbon / chiral silica (C / *SiO2@PAN) composite material.

[0073] (5) Preparation of pole piece:

[0074] The C / *SiO2@PAN composite material prepared in step (4) was mixed evenly with carbon black SuperP and polyvinylidene fluoride (PVDF) in a mortar at a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) was added. The mixture was homogenized at 2000 rpm for 30 min to obtain a slurry. The slurry was evenly coated on aluminum foil, dried in a vacuum drying oven at 80°C for 12 h, rolled, and sliced ​​to obtain a pole piece with a diameter of 12 mm.

[0075] (6) Assembly of sodium ion batteries:

[0076] The electrode prepared in step (5) was placed in a glove box for assembly of a 2032-type button battery. The specific operation was as follows: first, the sodium sheet was placed in the shell, then the glass fiber diaphragm was laid flat on the surface of the sodium sheet, and 160 μL of electrolyte (1M NaClO4in DMC: EC=1: 1 Vol%) was dripped to wet the diaphragm, then the electrode was placed on top of the diaphragm, and finally the gasket and the shrapnel were stacked on the surface of the electrode sheet in sequence. After completion, it was covered with a positive electrode shell and sealed with a battery sealing device. The packaged battery was left to stand for 12 hours before its electrochemical performance could be tested. The current density was set to 100 mA / g during the test.

[0077] Figure 1 This is the XRD pattern of the hard carbon material prepared in Example 1. Figure 1 It can be seen that there is no obvious characteristic peak in the XRD pattern of the hard carbon material, but at 23.5° and 42.5°, which correspond to the (002) and (100) crystal planes of amorphous carbon respectively, there is no characteristic peak of graphitized carbon, indicating that the hard carbon belongs to amorphous carbon.

[0078] Figure 2 and Figure 3 The BET diagrams of the hard carbon material prepared in Example 1 and the C / *SiO2@PAN composite material are shown in Figure 1. Figure 2 It can be seen from the adsorption-desorption curve that the adsorption amount of hard carbon material increases rapidly at a lower relative pressure, and the curve is convex. According to the BET calculation model, the specific surface area of ​​hard carbon is 1865 m2 / g; Figure 3 The specific surface area of ​​the C / *SiO2@PAN composite material obtained from the adsorption-desorption curve according to the BET calculation model is only 4.9945 m2 / g, indicating that the specific surface area of ​​the C / *SiO2@PAN composite material is significantly lower than that of the hard carbon material, and the specific surface area of ​​the material can be reduced by coating with PAN.

[0079] Figure 7 and Figure 8 The SEM images of the C / *SiO2 composite material and the C / *SiO2@PAN composite material prepared in Example 1 are shown respectively. Figure 7 It can be seen that the pores of porous hard carbon contain chiral silica materials, which play a supporting role and can well inhibit the volume expansion of silica during the electrochemical cycle. Figure 8 It can be seen that after coating PAN and carbonizing at high temperature, a dense layer of carbon is attached to the surface of the material, thereby reducing the specific surface area and alleviating the volume effect.

[0080] Examples 2 to 13 and Comparative Examples 1 to 6

[0081] The method of Example 1 was followed, except that the sucrose concentration, the amount of PAANa, the amount of ammonium fluoride, and the mass ratio of the precursor to KOH were changed, as shown in Table 1.

[0082] The hard carbon materials prepared in Examples 1 to 13 and Comparative Examples 1 to 6 and the assembled sodium ion batteries were tested for specific surface area, first cycle coulombic efficiency, and discharge specific capacity after 100 cycles, respectively. The results are shown in Table 1.

[0083] Table 1

[0084]

[0085] Note: The “specific surface area*” in Table 1 is the specific surface area of ​​the hard carbon material prepared in step (2).

[0086] From Table 1 we can see that:

[0087] When the sucrose concentration is 0.4 mol / L, the amount of PAANa is 0.4 g, the amount of NH4F is 0.3 g, and the mass ratio of the precursor to KOH is 1:2, the performance of the obtained battery is the best, the first cycle coulombic efficiency is 78.51%, and at a current density of 100 mA / g, the battery capacity can still maintain 265 mAh / g after 100 cycles. When the sucrose concentration increases from 0.2 mol / L to 1.0 mol / L, the capacity of the battery first increases and then decreases. With the increase of sucrose concentration, the cross-linked interpenetrating network formed by PAANa modification is more abundant, providing more abundant active sites for Na+, thereby increasing the battery capacity. However, when the sucrose concentration is too high, sucrose is more likely to agglomerate, and the structural part will change, resulting in a slight decrease in the cycle capacity.

[0088] When the sucrose concentration and NH4F dosage remain unchanged and the PAANa dosage is low, increasing the PAANa dosage can enrich the cross-linked interpenetrating network of the material, provide more abundant sites, and improve the capacity. However, when the PAANa dosage is further increased, the formed structure may be destroyed, resulting in structural collapse, which in turn leads to a decrease in the first coulombic efficiency and cycle performance of the prepared sodium-ion battery.

[0089] When the sucrose concentration, PAANa dosage, and the mass ratio of precursor to KOH were kept constant and the NH4F content was changed, it was found that when the NH4F dosage was 0.3 g, the pores formed were the largest and the battery capacity was also the largest. When the dosage was too high, the pores decreased and the battery capacity also decreased accordingly.

[0090] When the sucrose concentration, PAANa dosage, and NH4F dosage were kept unchanged and the mass ratio of precursor to KOH was changed, it was found that the pores formed were the largest when the mass ratio was 1:2. Too low a KOH dosage may result in insufficient pore size, and too high a KOH dosage may cause structural collapse, both of which are not conducive to the electrochemical performance of the battery. Therefore, when the sucrose concentration was selected as 0.4 mol / L, the PAANa dosage was 0.4 g, the NH4F dosage was 0.3 g, and the mass ratio of precursor to KOH was 1:2, the specific surface area of ​​the obtained hard carbon material was the largest, and the first-cycle coulombic efficiency and discharge capacity were both the largest at this time.

[0091] Figure 4 , Figure 5 and Figure 6 The SEM images of the hard carbon materials prepared in Example 1, Example 9 and Example 6 are shown respectively. Figure 4 It can be seen that the hard carbon material prepared in Example 1 has a rich pore structure, which is conducive to the loading of chiral silica and the embedding of Na+ ions in the electrochemical process. Figure 5 It can be seen that when the sucrose concentration increases to 1.0 mol / L, the sucrose will obviously aggregate and the porous structure will be destroyed, which may lead to a decrease in capacity. Figure 6 It can be seen that when the amount of PAANa increases to 1.0 g, the structure will also be damaged, which may cause the hard carbon matrix to be destroyed, the active sites to be reduced, and the capacity to be decreased.

[0092] Embodiments 14 to 18

[0093] The method of Example 1 was followed, except that the hydrothermal reaction temperature and time in step (1) were changed, as shown in Table 2.

[0094] The hard carbon materials prepared in Examples 14 to 18 and the assembled sodium ion batteries were tested for specific surface area, first cycle coulombic efficiency, and discharge specific capacity after 100 cycles. The results are shown in Table 2.

[0095] Table 2

[0096]

[0097] Note: The “specific surface area*” in Table 2 is the specific surface area of ​​the hard carbon material prepared in step (2).

[0098] It can be seen from Table 2 that under different hydrothermal reaction temperatures and reaction times, the specific surface area and electrochemical performance of the obtained products are not much different. When the hydrothermal reaction temperature is 170 ° C and the reaction time is 8 h, the specific surface area and electrochemical performance of the obtained product are the best.

[0099] Examples 19-20 and Comparative Examples 7-9

[0100] The method of Example 1 was followed, except that the concentration of TEOS in step (2) was changed, that is, the content of chiral silica in the composite material was changed, as shown in Table 3 for details.

[0101] The first cycle coulombic efficiency and discharge specific capacity after 100 cycles were tested for the C / *SiO2@PAN composite materials prepared in Examples 19 to 20 and Comparative Examples 7 to 9 and the assembled sodium ion batteries, and the results are shown in Table 3.

[0102] Table 3

[0103]

[0104] Note: The method for measuring the SiO2 content in the composite materials in Table 3 is: weigh the same weight of sample m0, place it in a muffle furnace for calcination, heat it at 800℃ for 5 h, remove the carbon in the composite material, and the remaining weight is the weight of *SiO2 m1, *SiO2 content = m1 / m0×100%.

[0105] As can be seen from Table 3, when the TEOS concentration increases, the content of SiO2 in the composite material will also increase accordingly, but it is not the case that the higher the SiO2 content, the better the performance of the resulting battery. Excessive SiO2 content will expand violently during the battery cycle, which will affect the battery performance. When the TEOS dosage is 1.10 mL, the resulting battery has the best performance. At this time, the first cycle coulomb efficiency is 78.51%, and at a current density of 100 mA / g, the battery capacity can still maintain 265 mAh / g after 100 cycles. As the TEOS content gradually increases, the content of the generated chiral silica will also gradually increase. If the silica content is too high, the volume expansion in the battery cycle will be more intense, resulting in a decrease in the battery capacity and cycle stability. When the silica content is too low, such as when the TEOS dosage is 0.55 mL, the effective capacity that can be provided is not enough, so when the TEOS dosage is 1.10 mL, it is most suitable and can provide the highest capacity.

[0106] Comparative Examples 10-12 and Examples 21-22

[0107] The method of Example 1 was followed, except that the mass ratio of the C / *SiO2 composite material to PAN was changed, as shown in Table 4.

[0108] The C / *SiO2@PAN composite materials prepared in Comparative Examples 10-12 and Examples 21-22 and the assembled sodium ion batteries were tested for specific surface area, first cycle coulombic efficiency, and discharge specific capacity after 100 cycles, and the results are shown in Table 4.

[0109] Table 4

[0110]

[0111] Note: The "specific surface area**" in Table 4 refers to the specific surface area of ​​the C / *SiO2@PAN composite material, and " / " means no PAN coating is used.

[0112] It can be seen from Table 4 that different proportions of PAN coating are related to whether the coating of the material is complete. After PAN coating, the specific surface area of ​​C / *SiO2@PAN is significantly lower than that of C / *SiO2 composite material. When the mass ratio of C / *SiO2 composite material to PAN is 1:2, the coating effect of the obtained material is the best. The small specific surface area can consume less electrolyte to form SEI film during the first discharge process, preventing further consumption of electrolyte, thereby increasing battery capacity and improving the first cycle coulomb efficiency.

[0113] Embodiment 23

[0114] The method of Example 1 was followed, except that the type of outer coating polymer was changed, and polyamic acid (PAA) was used instead of PAN to obtain a C / *SiO2@PAA composite material, as shown in Table 5.

[0115] The C / *SiO2@PAA composite material prepared in Example 23 and the assembled sodium ion battery were tested for specific surface area, first cycle coulombic efficiency, and discharge specific capacity after 100 cycles, and the results are shown in Table 5.

[0116] Table 5

[0117]

[0118] Note: The “specific surface area**” in Table 5 refers to the specific surface areas of the C / *SiO2@PAN composite material prepared in Example 1 and the C / *SiO2@PAA composite material prepared in Comparative Example 10, respectively.

[0119] It can be seen from Table 5 that the use of different types of polymers for coating can significantly reduce the specific surface area of ​​the material and improve the first-cycle coulombic efficiency of the battery. Among them, when the polymer is polyacrylonitrile, the coating effect is better and the resulting battery capacity is higher.

[0120] Embodiments 24 to 27

[0121] The method of Example 1 was followed, with the amount of the chiral inducer being maintained at 0.3 g. The difference was that the type of binder and the ratio of the binder to the chiral inducer were changed, as shown in Table 6 for details.

[0122] The sodium ion batteries assembled in Examples 24 to 27 were tested for first cycle coulombic efficiency and discharge specific capacity after 100 cycles. The results are shown in Table 6.

[0123] Table 6

[0124]

[0125] Note: “ / ” in Table 6 means the amount of binder is 0.

[0126] As can be seen from Table 6, the selection of different binders and different ratios of binders to chiral inducers will affect the battery performance. When the ratio of binder to chiral inducer is fixed at 1:1, when the binder is PEI, the first cycle coulombic efficiency and the capacity after the cycle of the obtained sodium ion battery are higher than those of PVA and PEG, which may be because the adhesion ability of PEI is stronger than that of PVA and PEG, which can make the structure more stable; when the amount of binder is 0, the battery performance is reduced, which may be due to the lack of the effect of the binder, resulting in the chiral inducer being unable to act on SiO2 and unable to generate chiral SiO2 materials, and thus the battery performance is slightly reduced.

[0127] Comparative Example 13 and Examples 28-32

[0128] The method of Example 1 was followed, except that the type and amount of the chiral inducing agent were changed, as shown in Table 7.

[0129] The sodium ion batteries assembled in Comparative Example 13 and Examples 28-32 were tested for first cycle coulombic efficiency and discharge specific capacity after 100 cycles. The results are shown in Table 7.

[0130] Table 7

[0131]

[0132] It can be seen from Table 7 that when the chiral inducer is changed to L-alanine, the electrochemical performance of the battery is slightly reduced compared with L-tartaric acid.

[0133] It can be seen from Table 7 that when the amount of inducer is different, the electrochemical performance of the material will also change. When the content of the chiral inducer is 0.3 g, the electrochemical performance of the battery is the best. When the content of the inducer is changed, the electrochemical performance of the battery decreases slightly. When the content of the inducer is zero, that is, no inducer is added, the electrochemical performance of the battery decreases significantly. This may be because the chiral SiO2 enhances the conductivity of SiO2 and can also alleviate the volume expansion of SiO2 to a certain extent, thereby improving the cycle efficiency and service life of the battery. When the chiral inducer is changed to L-alanine, the electrochemical performance of the battery is slightly reduced compared to L-tartaric acid. In the present invention, L-tartaric acid is preferably used as the chiral inducer.

[0134] Fig. 9 1 is the charge / discharge cycle curve of the sodium ion battery assembled with Example 1 and Comparative Example 13. Fig. 9It can be seen that under the condition of a current density of 100 mA / g, the first-cycle coulombic efficiency of the sodium ion battery assembled in Example 1 is 78.51%, and the discharge specific capacity is still 265 mAh / g after 100 cycles, and its coulombic efficiency is always close to 100% in the subsequent cycles; while the first-cycle coulombic efficiency of the sodium ion battery assembled in Comparative Example 13 is only 60.18%, and the discharge capacity is only 169 mAh / g after 100 cycles, and its cycle stability is far less than that of Example 1, which shows that the chiral material can effectively improve the electrochemical performance of the sodium ion battery during the battery cycle process.

[0135] Comparative Example 14

[0136] The method of Example 1 was followed, except that *SiO2 was used as the negative electrode active material to assemble a sodium ion battery, and the first cycle coulombic efficiency and discharge specific capacity after 100 cycles were tested. The results are shown in Table 8.

[0137] The preparation method of *SiO2 is: prepare a solution containing a chiral inducer according to the method of step (3) in Example 1, except that no hard carbon material is added when preparing solution A, and only the same amount of TEOS and ethanol are mixed to prepare solution A, and then react with solution B according to the method of step (3) in Example 1, centrifuge, wash, and dry to obtain pure *SiO2.

[0138] Table 8

[0139]

[0140] Fig.10 The battery charge and discharge cycle curves of the C / *SiO2@PAN composite material, C / *SiO2 composite material and pure *SiO2 material prepared in Example 1.

[0141] from Fig.10 It can be seen that both pure *SiO2 and C / *SiO2 composite materials without PAN coating on the outer layer show lower first-cycle coulombic efficiency and post-cycle capacity. The possible reasons are: when *SiO2 is not embedded in the hard carbon matrix, its volume expansion is not restricted, which greatly reduces its capacity; and when it is embedded in the hard carbon matrix without outer coating, volume expansion will also occur, resulting in a decrease in capacity, but the performance is improved compared with pure *SiO2.

[0142] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a carbon-coated hard carbon / chiral silica composite material, characterized in that: The following steps are involved: (1) hydrothermally reacting a carbon source, a modifier and a pore-forming agent to obtain a precursor; The carbon source is at least one of sucrose, glucose, fructose and maltose; the modifier is at least one of sodium polyacrylate and sodium carboxymethyl cellulose; the pore-forming agent is at least one of ammonium fluoride and ammonium chloride; the usage ratio of the carbon source, the modifier and the pore-forming agent is (0.2-1) mol: (0.15-1) g: (0.1-0.5) g; (2) mixing the precursor and the activator uniformly and then calcining at high temperature under the protection of an inert gas to obtain a hard carbon material; The activator is at least one of KOH, NaOH, K2CO3, ZnCl2, and H3PO4; the mass ratio of the precursor to the activator is 1:(1-3); (3) in a solution containing a chiral inducing agent, using silicate as a raw material, and using a sol-gel method to in-situ generate chiral silica in the pores of the hard carbon material to obtain a hard carbon / chiral silica composite material; The solution containing the chiral inducer is an aqueous solution of a binder and a chiral inducer; the binder is at least one of polyethyleneimine, polyvinyl alcohol and polyethylene glycol; the chiral inducer is at least one of L-tartaric acid, L-alanine, L-valine, L-lysine and L-glutamic acid; the mass ratio of the binder to the chiral inducer is 1:(0.1-2); (4) coating a polymer on the surface of the hard carbon / chiral silica composite material and carbonizing it at high temperature to obtain a carbon-coated hard carbon / chiral silica composite material, wherein the mass ratio of the hard carbon / chiral silica composite material to the polymer is 1:(1-3).

2. The method according to claim 1, characterized in that: In step (3), the sol-gel method uses water as solvent, ethanol as co-solvent, and acid or base as catalyst.

3. The method according to claim 1, characterized in that: In step (3), the reaction temperature of the sol-gel method is 60 to 80° C., and the reaction time is 2 to 12 hours.

4. The method according to claim 1, characterized in that: In step (4), the polymer is at least one of polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene glycol, phenolic resin, asphalt and polyamic acid.

5. The method according to claim 1, characterized in that: In step (4), the high temperature carbonization temperature is 800-1200° C., and the insulation time is 2-5 hours.

6. The method according to claim 1, characterized in that: In step (1), the temperature of the hydrothermal reaction is 150-170° C. and the time is 8-10 hours.

7. The method according to claim 1, characterized in that: In step (2), the high temperature calcination temperature is 700 to 1200° C., and the insulation time is 1 to 5 hours.

8. The carbon-coated hard carbon / chiral silica composite material prepared according to the method described in any one of claims 1 to 7 comprises a core and a shell, wherein the core is a hard carbon / chiral silica composite material, the shell is carbon, and the hard carbon / chiral silica composite material is a hard carbon material with embedded chiral silica.

9. Use of the carbon-coated hard carbon / chiral silica composite material according to claim 8 in sodium ion batteries and / or lithium ion batteries.

10. A sodium ion battery comprising a positive electrode, a negative electrode and a separator, wherein the negative electrode comprises a negative electrode active material, characterized in that: The negative electrode active material comprises the carbon-coated hard carbon / chiral silica composite material according to claim 8.